Population biology of European hake (Merluccius merluccius, Linnaeus, 1758) in Greece - Alexandros Theocharis; Maria Vlachou; Alexis Conides; Dimitris Klaoudatos (Academia Biology)
The European hake (Merluccius merluccius) is one of the most important demersal species in the Mediterranean Sea. A total of 861 individuals were collected using commercial bottom trawls, between May 2021 and October 2022 from the Aegean Sea (the Eastern Mediterranean) aiming to assess the current state of the population. The male to female ratio (0.92:1) did not significantly depart from 1:1, with length-weight relationships exhibiting positive allometric growth. There were seven age groups identified, with the second age group being the most predominate. The highest reproductive intensity was observed during spring followed by winter. The onset of sexual maturity (L50) for the total population was estimated at 27.58 cm in total length (3.2 years). The asymptotic length was estimated at 65.19 cm for the total population, with females growing larger than males. Longevity was estimated at 22.7 years for the total population (24.9 years for females and 16.1 years for males). The inflection point was estimated at 7.5 years for the total population (8.2 years for females and 5.2 years for males). Length with 50% probability of capture (LC50) was estimated at 17.7 cm, with the respective age (t50) of 1.2 years. The exploitation rate (E = 0.72) indicated that the population is under a high level of exploitation and the Z/K ratio (7.81) further indicated that mortality dominates growth. Fishing mortality at the maximum sustainable yield (FMSY = 0.29) was estimated considerably lower than the present fishing mortality (F = 0.69). Results indicate the need for enforcement of stricter management measures to protect the stock.